Impact of gastric emptying and small intestinal transit on blood glucose, intestinal hormones, glucose absorption in the morbidly obese - Nguyen, Nam Q; Debreceni, Tamara L; Burgess, Jenna E; Bellon, Max; Wishart, Judith; Standfield, Scott; Malbert, Charles-Henri; Horowitz, Michael (International Journal of Obesity, 2018)
Objective: This study evaluated gastric emptying (GE) and small intestinal (SI) transit in people with morbid obesity and their relationships to glycaemia, incretin hormones, and glucose absorption Methods: GE and caecal arrival time (CAT) of a mixed meal were assessed in 22 morbidly obese (50.2 ± 2.5 years; 13 F:9 M; BMI: 48.6 ± 1.8 kg/m 2 ) and 10 lean (38.6 ± 8.4 years; 5 F:5 M; BMI: 23.9 ± 0.7 kg/m 2 ) subjects, using scintigraphy. Blood glucose, plasma 3-O-methylglucose, insulin, glucagon, glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) were measured. Insulin sensitivity and resistance were also quantified Results: When compared with lean subjects, GE (t50: 60.7 ± 6.5 vs. 41.1 ± 7.3 min; P = 0.04) and CAT (221.5 ± 9.8 vs. 148.0 ± 7.1 min; P =  0.001) of solids were prolonged in morbid obesity. Postprandial rises in GIP ( P = 0.001), insulin ( P = 0.02), glucose ( P = 0.03) and 3-O-methylglucose ( P = 0.001) were less. Whereas GLP-1 increased at 45 mins post-prandially in lean subjects, there was no increase in the obese ( P = 0.04). Both fasting ( P = 0.045) and postprandial ( P = 0.012) plasma glucagon concentrations were higher in the obese Conclusions: GE and SI transit are slower in the morbidly obese, and associated with reductions in postprandial glucose absorption, and glycaemic excursions, as well as plasma GIP and GLP-1